The Desalination of Seawater from Jepara Beach uses Hollow Fiber Imprinted Membrane-Based Eugenol - Djunaidi, Muhammad Cholid; Maharani, Nesti Dwi; Khabibi, Khabibi; Susanto, Heru; Filardli, Abdullah Malik Islam (Universitas Jenderal Soedirman, 2025)
ABSTRACT. In 2022, Indonesia will experience a major problem with clean water, almost 119 million people do not have access to clean water and are forced to consume unsuitable water. This problem is caused by poor water management and the high cost of separating using a reverse osmosis membrane. The abundance of seawater in Indonesia and Jepara in particular has encouraged researchers to create alternative desalination membranes that are efficient and selective using Hollow Fiber Desalination Imprinted Membranes (HFDIM), which are available on the market with better quality. Hollow Fiber uses an imprinted method that has good efficiency and selectivity. The variations used in this research were variations in seawater dilution concentration of 0, 3, 5, and 10 times. In tensile, biodegradable, contact angle, TGA, porosity, water absorption, flux, and transport tests, the best results were obtained using HFDIM at varying concentrations of 10 times dilution solutions with a percentage of 86.67% in the receiving phase and 10.89% in the feed phase. on HFDNIM it is 48.33% in the receiving phase and in the feed phase it is 50%. Keywords: Desalination, hollow fiber, imprinted, polyeugenol